Non-Linear Association Between Serum Alkaline Phosphatase and 3-Month Outcomes in Patients With Acute Stroke: Results From the Xi'an Stroke Registry Study of China - Guo, Weiyan; Liu, Zhongzhong; Lu, Qingli; Liu, Pei; Lin, Xuemei; Wang, Jing; Wang, Yuanji; Chang, Qiaoqiao; Wang, Fang; Wu, Songdi (Frontiers in Neurology, 2022)
Background: Alkaline phosphatase (ALP) is associated with an increased risk of cardiovascular events and is closely related to adverse outcomes after stroke. However, regional investigation on the associations of ALP with acute stroke (AS) outcomes is limited. This study aimed to identify the association between serum ALP levels and clinical outcomes three months after AS in the Xi’an region of China. Methods: ALP levels and related patient information were collected at admission, and the events of stroke outcomes were followed up one and three months after diagnosis. ALP levels were analyzed as continuous variables and quartiles (Q1-Q4). The outcomes included all-cause mortality, recurrent stroke, and poor functional outcomes within three months. A multivariate logistic regression and interaction analyses were performed to evaluate the independent association between serum ALP level and three-month stroke outcomes. Results: Overall, 2,799 patients with AS were enrolled in this study. The mean age was 63.9 ± 12.5 years. In Q4 ( 93.0 U/L) group, the incidences of all-cause mortality, recurrent stroke and poor functional outcome were 7.8%, 2.7% and 24.9%, respectively. After adjusting for confounding variables, patients in Q4 ( 93.0 U/L) were related to an increased risk of all-cause mortality (odds ratio [OR] = 2.17, 95% CI: 1.19-3.96; P = 0.011) and patients in Q3 (76.8-92.9 U/L) were related to a lower risk of recurrent stroke (OR = 0.37, 95% CI: 0.14-0.97; P = 0.043) at the three-month time point, compared to those in Q2 (63.0-76.7 U/L). The optimal range of ALP for all-cause mortality was seen in Q2, with a nadir level of 70 U/L. However, differences were statistically insignificant between ALP levels and poor functional outcomes (P 0.05). Moreover, there was no significant interaction between ALP levels and age, gender, drinking status, smoking status or pneumonia (P 0.05) for all outcomes. Conclusion: Non-linear associations were observed between serum ALP levels and three-month outcomes in patients with AS. The optimal range of ALP for all-cause mortality was Q2 (63.0-76.7 U/L) with a nadir value of 70 U/L, and Q3 (76.8-92.9 U/L) was the optimal range of ALP for a recurrent stroke.